Analisis Proses Rekrutmen pada PT. Kereta Api Indonesia Daerah Operasional 9 di Jember - Najunda Sari Priawan; Dwi Windradini; Suhartono Suhartono (University of Jember, 2023)
This study aims to analyze the recruitment process carried out by PT. Kereta Api Indonesia DAOP 9 in Jember in order to meet the need for manpower. The method used is descriptive qualitative research by observing, interviewing, and direct documentation. The results of this study indicate that the recruitment process of PT. KAI is carried out by following the company's Workload globally. Recruitment conducted by PT. KAI is a process of fulfilling the need for workers in each branch office. Thus, in practice it does not prioritize the needs of each but prioritizes the needs of PT. Indonesian Railways as a whole. The implementation policy is carried out based on the results of the head office's considerations and decisions to obtain workers according to the existing qualifications and apply the same in each branch.